Pengaturan Hukum Tindak Pidana Pengambilan Paksa Jenazah Positif Covid 19 - Putu Ryan Baskara; Anak Agung Sagung Laksmi Dewi; Ni Made Puspasutari Ujianti (Jurnal Interpretasi Hukum, 2022)
Covid 19 is an acute respiratory tract infection caused by a virus called SARS-CoV-2. During the current pandemic, if a body dies in a positive state of COVID-19, a funeral will be carried out in accordance with health protocols. This study aims to find out how the legal regulation of the criminal act of forced retrieval of COVID-19 positive bodies and criminal sanctions for perpetrators of forced retrieval of COVID-19 positive bodies. This research uses a normative legal research method with a statutory approach, a case approach and a conceptual approach. Sources of data used are primary, secondary, tertiary data sources obtained from the recording and citation of relevant laws. The results of this discussion explain that the legal arrangement for the forced retrieval of Covid 19 bodies is regulated in Law Number 4 of 1984 on infectious disease outbreaks and perpetrators who forcibly take away the bodies of Covid 19 may be subject to criminal sanctions contained in Article 170 of the Criminal Code, Article 211 of the Criminal Code Jo. Article 335 of the Criminal Code jo. Article 336 of the Criminal Code jo. Article 93 of Law Number 6 of 2018 concerning Health Quarantine